Mediating roles of perceived social support and sense of security in the relationship between negative life events and life satisfaction among left-behind children: A cross-sectional study - Liu, Na; Li, Xinzheng; Ding, Xuemei; Liu, Haixia; Zhang, Xiaoli (Frontiers in Psychology, 2023)
Objective To determine the mediating roles of perceived social support and sense of security in the relationship between negative life events and life satisfaction among left-behind children (LBC). Methods A survey was conducted on 281 LBC in rural Shandong, China using negative life events, perceived social support, a sense of security, and life satisfaction scales. Results Negative life events were significantly negatively correlated with perceived social support, a sense of security, and life satisfaction (P<0.001). Perceived social support and a sense of security were significantly positively correlated with life satisfaction (P<0.001). The effect value of perceived social support on negative life events and life satisfaction was −0.21 (95% confidence interval [CI] = −0.32 to −0.14), with an indirect effect share of 33.33%. And the sense of security played an important role between negative life events and life satisfaction (β=−0.05, 95% CI = −0.11 to −0.01, percentage of effect = 7.94). The indirect effect of perceived social support and the sense of security between negative life events and life satisfaction was −0.03 (95% CI = −0.06 to −0.01), with an indirect effect share of 4.76%. Conclusion Negative life events could directly or indirectly affect the life satisfaction of LBC through the chain-mediating effects of perceived social support or the sense of security alone. Perceived social support and the sense of security are two important targets for further improving the life satisfaction of LBC.